ANALISIS BEBAN KERJA FISIK DALAM PENENTUAN WAKTU ISTIRAHAT PADA KARYAWAN WELDER PADA PT MCDERMOT INDONESIA - Dominggus Awola, Fernando; Zetli, Sri (Computer Science and Industrial Engineering, 2025)
This study aims to analyze the physical workload and determine the optimal rest time for welders at PT McDermott Indonesia using a physiological approach. Workload was measured through the Cardiovascular Load (CVL) method and energy consumption based on heart rates during work. The results showed that %CVL ranged from 30%–59%, categorized as "needs improvement." Most workers had energy consumption <5 Kcal/min, but three workers exceeded this threshold: two morning shift level-2 welders (Putra 5.07 Kcal/min; Hotmianto 5.05 Kcal/min) and one night shift level-4 welder (Deo 5.25 Kcal/min). These workers required additional rest times of 11.8 minutes, 8.5 minutes, and 38.7 minutes, respectively. Meanwhile, the standard 30-minute rest period was sufficient for others.